Hambatan Perencanaan Karir Mahasiswa Sebagai Generasi Milenial di Universitas KH. A. Wahab Hasbullah Jombang - Lailatus Sa’adah; Zawaidul Khair (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to determine the obstacles to student career planning in the economic faculty of the University of KH. A. Wahab Hasbullah Jombang. The research method used is a qualitative method with data collection observation, interviews and documentation, involving directly to students of the faculty of economics Wahab Hasbullah Jombang. Data analysis techniques including data reduction, data presentation and conclusion drawing. The results of this study the obstacles to career planning of students in the Faculty of Economics KH. A. Wahab Hasbullah Jombang are internal factors consisting of interest knowledge and physical condition while external factors consist of the influence of the family environment, minimal socio-economic status and the environment of student association with peers.